Clan Traditions and Popular Tales of the Western Highlands and Islands - Campbell, John Gregorson, 1836-1891; Nutt, Alfred Trübner, 1856-1910; MacIsaac, Duncan; Wallace, Jessie Campbell (Salt Lake City, UT : Project Gutenberg, 2022)
"Clan Traditions and Popular Tales of the Western Highlands and Islands" by John Gregorson Campbell et al. is a collection of folk tales and clan traditions written in the late 19th century. This volume encapsulates the rich oral traditions, legends, and tales of the Highland clans, presenting a vivid portrayal of the cultural heritage of the Scottish Highlands and Islands. It serves as a historical record of these tales, revealing the lives and beliefs of the people through their stories. At the start of the work, the reader is introduced to the life of John Gregorson Campbell, a minister who dedicated his life to capturing and preserving Gaelic folk tales. He collected stories that reflect the customs, aspirations, and historical narratives of the Scottish clans. The opening contains a rich tapestry of clan legends, such as the exploits and marriages of the MacLeans, and the adventures of notable figures like "Big Lachlan MacLean" and "Little John of the White Bag." These narratives not only entertain but also provide insights into the societal norms, moral lessons, and historical memories of the Highlanders. (This is an automatically generated summary.)
Release date is 2022-03-12
Susan Skinner, Thomas Frost and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Civilization, Celtic; Folklore -- Scotland -- Highlands; Oral tradition -- Scotland -- Highlands; Clans -- Scotland -- Highlands; Highlands (Scotland)